p27 Suppresses Arsenite-induced Hsp27/Hsp70 Expression through Inhibiting JNK2/c-Jun- and HSF-1-dependent Pathways - Liu, Jinyi (American Society for Biochemistry and Molecular Biology, 2010)
p27 is an atypical tumor suppressor that can regulate the activity of cyclin-dependent kinases and G(0)-to-S phase transitions. More recent studies reveal that p27 may also exhibit its tumor-suppressive function through regulating many other essential cellular events. However, the molecular mechanisms underlying these anticancer effects of p27 are largely unknown. In this study, we found that depletion of p27 expression by either gene knock-out or knockdown approaches resulted in up-regulation of both Hsp27 and Hsp70 expression at mRNA- and promoter-derived transcription as well as protein levels upon arsenite exposure, indicating that p27 provides a negative signal for regulating the expression of Hsp27 and Hsp70. Consistently, arsenite-induced activation of JNK2/c-Jun and HSF-1 pathways was also markedly elevated in p27 knock-out (p27(−/−)) and knockdown (p27 shRNA) cells. Moreover, interference with the expression or function of JNK2, c-Jun, and HSF-1, but not JNK1, led to dramatic inhibition of arsenite-induced Hsp27 and Hsp70 expression. Collectively, our results demonstrate that p27 suppresses Hsp27 and Hsp70 expression at the transcriptional level specifically through JNK2/c-Jun- and HSF-1-dependent pathways upon arsenite exposure, which provides additional important molecular mechanisms for the tumor-suppressive function of p27.